Nanobeacon: A time calibration device for the KM3NeT neutrino telescope - Aiello, S.; Domi, Alba; Albert, A.; Alshamsi, M.; Garre, S. Alves; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2022)
The KM3NeT Collaboration is currently constructing a multi-site high-energy neutrino telescope in the Mediterranean Sea consisting of matrices of pressure-resistant glass spheres, each holding a set of 31 small-area photomultipliers. The main goals of the telescope are the observation of neutrino sources in the Universe and the measurement of the neutrino oscillation parameters with atmospheric neutrinos. A relative time synchronisation between photomultipliers of the nanosecond order needed to guarantee the required angular resolution of the detector. Due to the large detector volumes to be instrumented by KM3NeT, a cost reduction of the different systems is a priority. To this end, the inexpensive Nanobeacon has been designed and developed by the KM3NeT Collaboration to be used for detector time-calibration studies. At present, more than 600 Nanobeacons have been already produced. The characterisation of the optical pulse and the wavelength emission profile of the devices is critical for the time calibration. The optical pulse rise time has been quantified as less than 3 ns, while the Full Width Half Maximum is less than 6 ns. The wavelength drift, due to a variation of the supply voltage, has also been qualified as lower than 10 nm for the full range of the Nanobeacon. In this paper, more details about the main features of the Nanobeacon design, production and operation, together with the main properties of the light pulse generated are described.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Instrumentation; Neutrino telescopes; Time calibration